Impact of livestock and settlement on the large mammalian wildlife of Bale Mountains National Park, southern Ethiopia - Stephens, P; d'Sa, C; Sillero-Zubiri, C; Leader-Williams, N (2001)
Large mammals, both wild and domestic, were censused in four study areas in Bale Mountains National Park (BMNP), southern Ethiopia, from April until August 1997, using established road counts, horse-back counts and systematic transects, a new approach to censusing large mammals in BMNP. Data collected since 1983 were also examined to indicate trends in mammalian abundance. Civil unrest following the government changeover in 1991 disrupted management of BMNP, leading to an increase in human settlement and livestock densities. The effect of these factors on BMNP's wildlife is assessed and discussed. Most large mammalian wildlife has declined since 1983 but signs of recovery for some species in recent years are positive. The fates of two charismatic endemics are emphasised. BMNP's current population of mountain nyala (Tragelaphus buxtoni, an endangered antelope) was estimated to be between 1100 and 1300. This is lower than estimates for the late 1980s, but shows an increase from very low levels recorded following social turmoil during the government changeover in 1991. Data on the Ethiopian wolf (Canis simensis, a critically endangered canid) also indicate positive trends in abundance, following severe declines between 1989 and 1992 due to rabies epizootics. Action to reduce human utilisation of parts of BMNP is urgently required to prevent further degradation of the environment and to safeguard the future of both the mountain nyala and Ethiopian wolf. © 2001 Elsevier Science Ltd. All rights reserved.